Measuring Portfolio Risk in Options - Sears, R. Stephen; Trennepohl, Gary L. (Journal of Financial and Quantitative Analysis, 1982)
Little attention has been given to the behavior of option portfolio risk across different portfolio sizes, perhaps because many individuals view unhedged long option positions as too risky for rational investor consideration. It appears possible, however, to combine long option positions with less risky assets to produce portfolios with favorable risk-return characteristics [10].